Mental fatigue alters the speed and the accuracy of the ball in table tennis. Issue 23 (2nd December 2018) - Le Mansec, Yann; Pageaux, Benjamin; Nordez, Antoine; Dorel, Sylvain; Jubeau, Marc
ABSTRACT: This study aimed at evaluating the effects of mental and muscle fatigue on table tennis performance. Mental fatigue (MF) was induced by completion of 90 minutes of the AX-CPT; muscle fatigue was induced by completion of an eccentric exercise performed with the elbow flexors (biceps fatigue, BF) or the knee extensors (quadriceps fatigue, QF). The control condition consisted of watching a movie. Stroke parameters (speed and accuracy of the ball), as well as feelings of fatigue and force production capacity of the elbow flexors (BF, MF and control conditions) and knee extensors (QF condition), were assessed pre and post fatigue protocols. Feelings of fatigue increased post fatigue protocols. Force production capacity decreased only in the BF and QF conditions. BF and MF induced a decrease in accuracy. This decrease in accuracy was associated with an increased ball speed in the BF condition, and a decreased ball speed in the MF condition. QF had a negligible effect on stroke performance. Our results suggest that both mental fatigue, and muscle fatigue, significantly impair table tennis performance and therefore coaches should take into account both the physical and mental state of table tennis players to optimize performance.